The best writing on mathematics 2011 [ - Pitici, Mircea , 1965- (Princeton University Press, 2012)
Discusses the features that distinguish mathematics from other disciplines of the mind. This title identifies some of the mathematical inspirations of M C Escher's art. It describes compressed sensing, a mathematical field that reshapes the way people use large sets of data. It reports on the use of algorithms in the job market for doctors